Promoting Gender Equality and Empowerment: A Quranic and Hadith Perspective on Women's Roles in Islam - Ida Afidah (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The Quran and the Hadith or prophetic traditions have defined the goal of Syariah as the manifestation of fairness and goodness. The Quran is a legal resource containing universal values guiding human life. Both women and men are essential beings. However, cultural, political, and interpretive power often make Islam seem unfriendly and discriminatory towards women. This study examines and analyses women's existence from an Islamic perspective. Specifically, this study will discuss women's existence in the discourse of gender equality, women's role in the domestic sphere, women's role in the public sphere, and the discourse on the future of women involving Islamic perspectives. The research method used is a literature review, specifically a study of Quranic and Hadith perspectives on gender roles and equality in Islam. The author systematically reviewed relevant literature, including Quranic verses, Hadith texts, and scholarly interpretations of these sources. The study's findings show that numerous verses in the Qur'an and Hadiths emphasize the equal status of men and women in the eyes of God and the need for justice and fairness in all aspects of life, including gender relations, women's role in the domestic sphere, and women's role in the public sphere. Women's participation in domestic and public life is essential for the country's development and progress towards a better future, particularly in Indonesia. Therefore, it is crucial to continue exploring and analyzing the different perspectives on women's roles in Islam, including in the domestic and public spheres, to promote gender equality and empowerment. This can be achieved through the development of more progressive fiqh that considers the evolving needs and roles of women in society.